Itinéraires des voyageurs - Orlandini Carcreff, Alessandra (Presses universitaires de Provence, 2021)
Giuseppe ACERBI (1773-1846) Léonie d’AUNET (1820-1879) John BARROW (1764-1848) J. de BEAUREGARD (1844-1928) Jacques-Henri BERNARDIN DE SAINT-PIERRE (1737-1814) Pierre Marie Louis de BOISGELIN DE KERDU (1758-1816) Giacomo BOVE (1852-1887) John BOWRING (1792-1872) Selina BUNBURY (1802-1882) Théophile.